Synthesis and electrochemical characterization of iron oxide/poly(2-methylaniline) nanohybrids for supercapacitor application - Ahmed Ashour M.; Essam Doaa; Kabatas Mohamed A. Basyooni-M.; Abdel-Khaliek Ahmed A.; Shaban Mohamed; Aljaafreh Mamduh J.; Rabia Mohamed (Nanotechnology Reviews)
This study reports the synthesis of a nanohybrid material composed of poly(2-methylaniline) (P(2MA)) and iron oxide (Fe2O3) as electrodes for supercapacitors using a simple and cost-effective method. Various characterization techniques were employed to analyze the samples. The results revealed that the Fe2O3/P(2MA) nanohybrid exhibits nanofiber structures, while pure P(2MA) displays a porous hollow sphere morphology. Furthermore, the analysis confirmed the effective dispersion of Fe2O3 nanoparticles within the polymer matrix. The electrochemical properties of the Fe2O3/P(2MA) nanohybrid were found to surpass those of pure P(2MA) in both NaCl and HCl electrolytes. Notably, the nanohybrid demonstrated longer discharge times and higher oxidation/reduction currents in HCl than NaCl. The gravimetric and areal capacitances were measured at 998.4 F g−1 and 1497.6 mF cm−2 in 0.5 M HCl at a current density of 0.6 A g−1. Furthermore, the nanohybrid retained 99.9% of its initial specific capacitance after 2,000 cycles. These findings underscore the significant potential of the Fe2O3/P(2MA) nanohybrid as a high-performance supercapacitor electrode for energy storage applications.